Effectiveness of Active Music Therapy on Echolalia and Pitch Frequency in Level-One Autism Spectrum Disorder Children - Ahmadizade, Fahimeh; Mousavi, Said Ali mohammad; Babakhani , Narges (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to determine the effectiveness of an active music therapy protocol on reducing echolalia and improving pitch frequency among children with Level-One Autism Spectrum Disorder. This semi-experimental study employed a pretest–posttest design with a control group. Twenty-two children aged 4–7 years with Level-One ASD were selected through convenience sampling and randomly assigned to either an active music therapy group or a control group. The intervention was delivered across eight weeks using structured rhythmic, vocal, and auditory–motor activities. Echolalia was assessed using the Aberrant Behavior Checklist (Echolalia subscale), and pitch-related prosodic features were analyzed using Praat acoustic software. Data were collected across pretest, posttest, and follow-up phases. Statistical analysis was conducted using two-way repeated-measures ANOVA and Bonferroni-adjusted post-hoc tests. Repeated-measures ANOVA revealed a significant time × group interaction for pitch frequency, indicating greater improvement in the active music therapy group compared with controls across posttest and follow-up (p < .05). The intervention group showed a marked increase in pitch frequency from pretest to follow-up, while the control group demonstrated no meaningful change. Echolalia scores exhibited a significant reduction in the experimental group compared with the control group over time (p < .05), confirming the therapeutic effect of rhythmic–vocal engagement. Bonferroni post-hoc comparisons further indicated that the most substantial improvements occurred between pretest and follow-up in the therapy group, with effect sizes in the moderate-to-large range. Active music therapy produced significant improvements in prosodic features—particularly pitch frequency—and reductions in echolalia among Level-One ASD children, with gains maintained over time. The findings highlight the value of rhythmic, auditory–motor, and vocal synchronization activities for enhancing speech-related outcomes in this population.